Potassium Alkoxide/Disilane-Mediated Dehalogenative Deuteration - Wang, Xin; Zhu, Ming-Hui; Liu, Wen-Bo (Synlett, 2019)
Deuterated compounds are of great importance in chemistry and pharmaceuticals. Reductive dehalogenation is one of the most useful methods to incorporate deuterium into molecules. This article briefly discusses the historical development of dehalogenative deuteration reactions that involve transition-metal catalysis, radical halogen abstraction, alkali-metal reductive deuteration, and the recently developed potassium methoxide/hexamethyldisilane-mediated dehalogenation of aryl halides.
Keywords: deuteration; dehalogenation; aryl halides; Transition-metal-free; potassium base; disilane